Asuhan Keperawatan pada Ny. K dan Ny. N yang Mengalami Nyeri Akut dengan Unstable Angina Pectoris di RSUD dr. Chasbullah Abdulmadjid Kota Bekasi - Bella, Silsa; Vestabilivy, Evi; Fatkhurroman, Mohammad (STIKes Persada Husada Indonesia, 2024)
Unstable Angina Pectoris is a condition that disrupts the heart's ability to pump blood. Angina Pectoris is a condition of chest pain or discomfort caused by coronary artery disease. The general aim of this research is to obtain an overview of the implementation of nursing care for patients experiencing acute pain with unstable angina pectoris. This research design uses descriptive qualitative research with a case study approach with intervention using rhythmic breathing techniques. Participants in this case were patients at Dr. Chasbullah Abdulmadjid Regional Hospital, Bekasi City, namely 2 patients, 2 family members, and 1 nurse and patients aged 19 years to 70 years. The characteristics of the patients who were the subjects of this research were patients who had been diagnosed with Unstable Angina pectoris and had the same nursing problem, namely acute pain. The results of the assessment showed complaints of chest pain, shortness of breath, headaches. Based on this data, 4 similar diagnoses were found. Nursing diagnosis for Mrs. K and Mrs. N is acute pain, ineffective breathing patterns related to hyperventilation, activity intolerance, anxiety. Another diagnosis for Mrs. N is sleep pattern disturbance. The main planning carried out by Mrs. K and Mrs. N encourage deep breathing and monitor the pain scale. The aim is to carry out 3 x 24 hours for each nursing diagnosis. The main nursing action taken to reduce pain is the rhythmic breathing distraction technique. Evaluation, the acute pain nursing problem has been resolved. In carrying out nursing care for clients with angina pectoris, it is recommended to use rhythmic breathing distraction techniques more effectively.